Idiomatic Expression in the “Maleficent (Mistress of Evil)” Movie - Fina Amalia Masri; Randi; Ela Martisa (Jurnal Multidisiplin Madani, 2022)
Idiomatic expression has an important role in constructing formative sentences. The aim of this research is to describe the idiomatic expression based on their forms and meanings. The descriptive qualitative method was used in this research; the data had been taken from the movie and analyzed them based on the Boatner and Gates theory. Technique of data collection was done by downloading, reading, watching, classifying and coding the data. After collecting the data, it was analyzed by presenting the data, describing the data, interpreting the data, and concluding. The results of this research showed that 16 idiomatic expressions found in Maleficent (Mistress of Evil) movie that classified in 3 forms, namely 9 lexemic idiomatic expression, which are divided in 4 classes, 1 verb idiomatic expression, 6 noun idiomatic expressions, 1 adjective idiomatic expression, 1 adverb idiomatic expression, 3 phrase idiomatic expressions, and 4 proverbs. Researcher found many idiomatic expressions in the form of nouns because in the movie all characters use explanatory adverbs where the noun functions as a participle. In a sentence, a noun can act as the subject, direct object, and indirect object of a clause, and can be a subject complement or object complement